2020
DOI: 10.1371/journal.pone.0233631
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis for the difference in carotenoids accumulation in flesh and peel of white-fleshed loquat fruit

Abstract: Loquat (Eriobotrya japonica Lindl.) is divided into yellow-and white-fleshed based on the difference in fruit color, and the variations in carotenoids accumulation are considered as the main reasons for this difference. Using RNA-seq technology, a transcriptome analysis was carried out on the flesh and peel of 'Baiyu' fruit during four different fruit development stages. A total of 172.53 Gb clean reads with an average of 6.33 Gb reads were detected for each library, and the percentage of Q30 was higher than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…More interestingly, TBW demonstrated the capacity to accumulate a certain amount of carotenoids in its mature flesh, which is far higher than that of the existing white-fleshed loquat varieties ( Liu et al., 2016 ). The white flesh trait in loquat has been confirmed to be controlled by a single recessive gene, which leads to the inability of normal accumulation of carotenoids in white-fleshed loquats ( Fu et al., 2014 ; Zou et al., 2020a ; Song et al., 2022b ). However, our findings suggest that bud sport did not completely block the synthesis of carotenoids in the flesh of TBW, which enhanced its nutritional value and breeding potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, TBW demonstrated the capacity to accumulate a certain amount of carotenoids in its mature flesh, which is far higher than that of the existing white-fleshed loquat varieties ( Liu et al., 2016 ). The white flesh trait in loquat has been confirmed to be controlled by a single recessive gene, which leads to the inability of normal accumulation of carotenoids in white-fleshed loquats ( Fu et al., 2014 ; Zou et al., 2020a ; Song et al., 2022b ). However, our findings suggest that bud sport did not completely block the synthesis of carotenoids in the flesh of TBW, which enhanced its nutritional value and breeding potential.…”
Section: Discussionmentioning
confidence: 99%
“…Loquat ( Eriobotrya japonica L.) is an evergreen fruit tree of the Rosaceae family, which can be classified into yellow- and white-fleshed types based on the flesh color ( Jing et al., 2022 ). Yellow-fleshed loquat displays an orange or orange-red flesh color due to its high levels of carotenoids ( Zou et al., 2020a ). Moreover, yellow-fleshed varieties generally possess a denser flesh composition, thicker skin, stronger resistance to storage, and higher average fruit weight ( Jiang et al., 2015a ; Zou et al., 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid biosynthesis is a well-studied secondary metabolic pathway in plants, known to be involved in the production of various pigments ( Grotewold, 2006 ; Wang et al., 2023 ). Carotenoids, on the other hand, have received substantial research attention in horticultural crops, such as loquat ( Zou et al., 2020 ), corn (Wang et al., 2020), and mango ( Petry and Mercadante, 2016 ). In our study, a total of 267 flavonoids and 35 carotenoids were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Se observó un aumento en el contenido de carotenoides junto con una mayor capacidad de almacenamiento, pero sin cambios significativos en la expresión de los genes OR o PSY (Jaramillo et al, 2022). La coliflor con el gen Or acumuló un alto nivel de β-caroteno en los botones florales y se volvió de color naranja, pero este aumento de β-caroteno no se debió a la alta capacidad de biosíntesis de carotenoides (Zou et al, 2020).…”
Section: Condiciones Que Afectan La Acumulación De Carotenoides En Pl...unclassified